Intraparietal sulcus activity during explicit self-referential social status judgments about others - Jasmin Cloutier (Universidad de San Buenaventura, 2013)
Previous research has suggested that the intraparietal sulcus (IPS) supports judgments of social distance, with greater activity observed in response to targets judged to be closer to each other (Yamakawa, Kanai, Matsumura, & Naito, 2009). Amongst other stimuli, activity in the IPS appears to be responsive to targets varying in social status (Chiao et al., 2009; Cloutier, Ambady, Meagher, & Gabrieli, 2012). The current project examined brain responses during explicit self-referential social status judgments of targets varying in either financial or moral status. Using an event-related fMRI design, participants viewed photographs of male faces paired with distinct levels of financial or moral status. During the task, participants were asked to explicitly identify each target’s status in relation to their own. Focusing on IPS activity, results from whole-brain and region of interest analyses revealed an interaction between social status types and levels. The implications of these results are discussed with respect to our current understanding of the impact of social status on the neural substrates of person perception.